PENGARUH FS, NWC, DAR, SG, DAN CF TERHADAP CASH HOLDINGS - Listiani, Reva; Susanti, Merry (Jurnal Paradigma Akuntansi, 2025)
This project aims the purpose of receiving empirical evidence about the effect of firm size, net working capital, leverage, sales growth, and cash flow on cash holdings in property and real estate subsector companies listed on the Indonesia Stock Exchange for 2019-2021 period. Sampling was carried out in this project using purposive sampling. 35 property and real estate subsector companies with a period of three years were obtained as sample in this project. The type of data used in this study was secondary data obtained from financial reports published on the Indonesian Stock Exchange website and related company websites. Data processing techniques using multiple linear regression analysis contributed by Microsoft Excel and Eviews 12 program. The results showed that firm size had a positive and significant effect on cash holdings, while net working capital, sales growth, and cash flow had a positive and insignificant effect in cash holdings, and leverage had a negative and insignificant effect on cash holdings. The research’s implication is that corporation require to manage cash in order to develop strategies so that companies can earn bigger profits.